2015
DOI: 10.1590/0001-3765201520140111
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and evaluation of antimicrobial and cytotoxic activity of estragole, obtained from the essential oil of croton zehntneri (euphorbiaceae)

Abstract: Croton zehntneri (Euphorbiaceae) is a native aromatic plant from Northeast region of Brazil. The monoterpenoid estragole (ESL) has been isolated by classical chromatographic methods from the essential oil (EO) of C. zehnteneri leaves and characterized by GC-FID and GC-MS, its antimicrobial and cytotoxic potentials being assessed. The analysis of the EO enabled the identification of 100% of the integrated constituents, of which yield was about 1.8%. The main components identified were: eucalyptol, estragole (84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Plants from the Euphorbiaceae family have also demonstrated antimicrobial activity. Croton zehntneri and Manihot multifida (L.) Crantz had potential activity against several positive and negative gram strains, inhibiting up to 73.5% of S. aureus and 72.72% of E. coli growth, respectively (Kirbag et al, 2013; Andrade et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Plants from the Euphorbiaceae family have also demonstrated antimicrobial activity. Croton zehntneri and Manihot multifida (L.) Crantz had potential activity against several positive and negative gram strains, inhibiting up to 73.5% of S. aureus and 72.72% of E. coli growth, respectively (Kirbag et al, 2013; Andrade et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also reported that oils containing high concentrations of estragole have antifungal activity. For example, croton zehntneri oil, which contains 84.7% estragole produced significant zones of inhibition against fungi ( C. albicans and B. dermatitidis ) 45 . The essential oil extracted from Foeniculum vulgare , which contains a major fraction of estragole, demonstrated antifungal activity against C. albicans 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar investigation, essential oil of Croton zehntneri, containing its major compound estragole, was tested on NCI-H292, MCF-7 and Hep-2 cell lines. Results revealed numbers lower than 20% of growth inhibition (Andrade et al, 2015). This study demonstrates that the physical-chemical profile of the extract is composed of phenolic compounds, flavonoids, and hydrolysed tannins.…”
Section: Resultsmentioning
confidence: 65%
“…Percentage values of 1-20% were classified as "without inhibitory activity", between 20-50% as "low inhibitory activity", for values between 50-70% as "moderate inhibitory activity", and as "high inhibitory activity" for 70-100% (Andrade et al, 2015).…”
Section: Resultsmentioning
confidence: 99%